ANALISIS PENGARUH RASIO KEUANGAN TERHADAP HARGA SAHAM PADA PERUSAHAAN OTOMOTIF YANG TERCATAT DI BURSA EFEK INDONESIA (BEI) PERIODE 2012-2014 - Nur Hastuti; Aftoni Sutanto (Universitas Ahmad Dahlan, 2017)
This research aims to test the influence C (Current Ratio), IT (Inventory Turnover), DER (Debt Equity Ratio), ROI (Return On Investment), and ROE (Return On Equity) to the stock price on the automotive industry which is listed on the Stock Exchange Indonesia in 2012-2014. The sample in this study is the automotive company. The sampling technique in this study using purposive sampling technique, obtained 12 samples of automotive companies. The test using statistical test multiple linear regression analysis. Partially, the statistical test used was the t test, simultaneously with the F test and the coefficient of determination (R2). Based on the results of this study concluded that the partial CR (Current Ratio), IT (Inventory Turnover), DER (Debt Equity Ratio), ROI (Return On Investment), and ROE (Return On Equity) does not affect the value of automotive companies, and simultaneous no effect on the stock price at the automotive company 2012-2014. R-Squared value (R2) of 0.200 (20.0%) means that the independent variables affect the dependent variable of 20.0% and 80.0% side explained by other variables outside the model.